Risk factors associated with vertical transmission of the human immunodeficiency virus during gestation - Moreno Reyes, Katherin Faviola (2021)
Infection by the human immunodeficiency virus (HIV) continues to be a perinatal health problem globally and in our country, due to the increase in contagion in pregnant women who run the risk of vertical transmission of HIV to their baby during the pregnancy, childbirth and breastfeeding. Various publications mention that the prevalence of vertical transmission of HIV varies according to different authors between 3.8% and 17%. In Peru it is reported at 4%. Among the risk factors associated with vertical transmission of HIV, the following are mentioned: absence of antiretroviral therapy during prenatal care with adjusted odds ratio (aOR) ranging from 2.41 to 17.20; absence of a program for the prevention of mother-to-child transmission of HIV with aORa of 4.6 to 40.6; absence of prenatal control ORa 4.6; home delivery with aOR of 3.35 to 8.10; emergency cesarean delivery with OR of 4.32; absence of antiretroviral prophylaxis to the newborn ORa of 3.4 to 5.83 and high viral load in pregnancy between 4.0% to 8.5%. Keywords: Risk factors; Vertical transmission of HIV; Human immunodeficiency virus; HIV infection during pregnancy